1968
DOI: 10.1017/s0031182000069353
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low protein diet and a glucose and filter paper diet on the course of infection ofNippostrongylus brasiliensis

Abstract: Rats were fed on two deficient diets and were infected with N. brasiliensis larvae. They were autopsied at times ranging from 18 hours to 17 days after infection. The effect of the diets on worm burden, sex ratio of the worms and size of larvae and of worms were noted. Significantly more larvae reached the lungs and intestine in rats fed on glucose and filter paper (G.F.P.) and low protein (L.P.) diets than in controls, the highest numbers coming from G.F.P. rats. Neither the migration rate nor the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Protein supplementation is often associated with higher levels of eosinophils and other immune mediators (Coop and Kyriazakis, 2001;Koski and Scott, 2001). Despite the positive effects of protein limitation on adult survival and egg shedding in several single infection studies of both N. brasiliensis (Clarke, 1968;Jones et al, 2009), and H. p. bakeri (Boulay et al, 1998;Ing et al, 2000;Tu et al, 2007), the effects of protein limitation on eosinophils were less consistent across previous mouse experiments. For example, many studies detected no difference in eosinophils among treatments with differing protein content (Ing et al, 2000;Tu et al, 2007;Jones et al, 2009), while others found that eosinophil levels were highest at an intermediate protein level (7% protein) compared with low (3%) and high (24%) protein treatments (Boulay et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…Protein supplementation is often associated with higher levels of eosinophils and other immune mediators (Coop and Kyriazakis, 2001;Koski and Scott, 2001). Despite the positive effects of protein limitation on adult survival and egg shedding in several single infection studies of both N. brasiliensis (Clarke, 1968;Jones et al, 2009), and H. p. bakeri (Boulay et al, 1998;Ing et al, 2000;Tu et al, 2007), the effects of protein limitation on eosinophils were less consistent across previous mouse experiments. For example, many studies detected no difference in eosinophils among treatments with differing protein content (Ing et al, 2000;Tu et al, 2007;Jones et al, 2009), while others found that eosinophil levels were highest at an intermediate protein level (7% protein) compared with low (3%) and high (24%) protein treatments (Boulay et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…A more detailed study of the effect of deficient diets on the course of N. brasiliensis (Travassos, 1914) infections has been reported elsewhere; the reasons for the earlier elimination of the parasites by rats on these diets has been discussed in the same paper (Clarke, 1968). …”
mentioning
confidence: 94%
“…All these studies, however, have been carried out using adequately nourished, healthy rats as hosts. Evidence is accumulating of the synergistic effect of malnutrition and infection (Scrimshaw, Taylor & Gordon, 1968) and, although much of this work has been related to bacterial infections, experiments by Wells (1962), Clarke (1968) and Bolin, Davis, Cummins, Duncombe & Kelly (1977) have indicated that the rejection of N. brasiliensis is impaired in protein-malnourished rats. In addition Bonn et al (1977) made a preliminary examination of the intestine and observed that partial villus atrophy was evident up to day 28 of the infection when the experiment was terminated.…”
Section: Introductionmentioning
confidence: 99%